PM2.5-bound Polycyclic Aromatic Hydrocarbons in Ho Chi Minh City, Vietnam: Potential Sources, Health Risks, and Deposition Flux - Nguyen Doan Thien Chi; Duong Huu Huy; Nguyen Thao Nguyen; Ly Sy Phu Nguyen; Tran Anh Ngan; Norimichi Takenaka; To Thi Hien (Aerosol and Air Quality Research)
Abstract Exposure to fine particulate matter (PM2.5)-bound polycyclic aromatic hydrocarbons (PAHs) can have severe impacts on the inhabitants of polluted cities. To characterize the variation of PM2.5-bound PAHs in the urban area of Ho Chi Minh City (HCMC), the biggest city in southern Vietnam, we conducted a whole year sampling campaign. The sampling strategy for PM2.5-bound PAHs was deployed from March 2017 to March 2018 at six locations in HCMC. The sampling sites represented traffic emissions, residential areas, an urban background location, and a rural background location. The results showed that five- and six-ring PAHs predominated in PM2.5, accounting for approximately 70% of the total PAHs concentrations. Benzo(g,h,i)perylene (BghiP) and indeno(1,2,3-cd)pyrene (InP) were the dominant species, contributing about 53% to the total PAHs. The seasonal variation of PAHs exhibited two peaks in May and December and dramatically dropped in March. We found significant negative correlations between PAHs and meteorological factors such as solar radiation, wind speed, and planetary boundary layer. This suggests an important role of meteorological factors in scavenging PAHs in urban HCMC. The positive matrix factorization (PMF) results reflected that vehicular emissions are the major local source of PM2.5-bound PAHs in urban HCMC. Additionally, the concentration weight trajectory approach (CWT) revealed that regional sources from the northeast area of HCMC contributed a large amount of medium molecular weight, high molecular weight, and total BaP equivalent (BaPTEQ). Furthermore, PM2.5-bound BaPTEQ significantly accumulated in the alveolar tissues of the human respiratory system.